2012
DOI: 10.1007/s10719-012-9377-2
|View full text |Cite
|
Sign up to set email alerts
|

Phosphorylated modification and in vitro antioxidant activity of Radix Hedysari polysaccharide

Abstract: Phosphorylated modification of a polysaccharide obtained from Radix Hedysari (RHP) was studied. Three phosphorylated polysaccharides (RHPP) with variable degrees of substitution (DS(p)) were obtained with 4-dimethylaminopyridine (DMAP) and N, N' Dicyclocarbodiimide (DCC) as catalyst. The structures of RHPP were characterized by FT-IR spectra and (13)C NMR spectra. Depending on different reaction time, RHPP showed different DS(p) ranging from 0.30 to 0.66, and different Mw ranging from 86.6 to 89.7 KDa. Compare… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
18
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(19 citation statements)
references
References 20 publications
1
18
0
Order By: Relevance
“…The RHP was purified by the Institute of Combined Traditional Chinese and Western Medicine, School of Basic Medical Science at Lanzhou University (Lanzhou, China) (6,9). The polysaccharide content was 97.3%.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The RHP was purified by the Institute of Combined Traditional Chinese and Western Medicine, School of Basic Medical Science at Lanzhou University (Lanzhou, China) (6,9). The polysaccharide content was 97.3%.…”
Section: Methodsmentioning
confidence: 99%
“…Radix Hedysari polysaccharide (RHP) is the main bioactive ingredient of RH, and possesses several pharmacological activities, including antitumor, anti-inflammatory, antioxidant and immunomodulatory effects (6,7). Previous studies have also suggested that RHP may have hypoglycemic and hypolipidemic properties and may improve insulin resistance (8), however, the effect of RHP on NAFLD remains to be elucidated.…”
Section: Introductionmentioning
confidence: 99%
“…However, these systems are insufficient to prevent the harm entirely [4]. It is reported that free radicals, including superoxide anion, hydroxyl radical, and hydrogen peroxide can cause pathological damages like cancer disease, diabetes, atherosclerosis, coronary heart disease, and many other diseases associated with aging to the organism, and lead to harmful alterations in foods and pharmaceutical industries [5][6][7]. Therefore, it is urgent to develop antioxidant supplements to help the human body reduce oxidative scratch.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, a “C–O–S” bond would give rise to the FT-IR band observed at 810 cm −1 (Figure 2c) [13], indicating that the successful sulfation of lentinan. The phosphorylation of lentinan was also confirmed by FT-IR of P-D. Three new strong absorption peaks appeared in the P-D spectrum at 1720, 1270, and 790 cm −1 , and these were assigned to “C=O” stretching vibration, “P=O” asymmetric stretching, and “C–O–P” symmetric vibrations, respectively (Figure 2d) [14]. These absorptions indicated that the phosphorylated modification of lentinan was successfully performed.…”
Section: Resultsmentioning
confidence: 88%
“…Lentinan was phosphorylated following the procedure described by Wei et al [14]. Lentinan (0.5 g) was suspended in anhydrous N , N -Dimethylformamide (DMF) (20 mL) at room temperature under stirring for 30 min.…”
Section: Methodsmentioning
confidence: 99%